CHAPTER NINE ORGANIC-WALLED DINOFLAGELLATE CYSTS: TRACERS OF SEA-SURFACE CONDITIONS - Vernal A.d.; Marret F. (My University, 2007)
Dinoflagellates are microscopic unicellular organisms belonging to the division of Dinoflagellata. They inhabit most types of aquatic environments, from lakes to open ocean, and occur at all latitudes from the Equator to Polar seas. Together with diatoms and coccolithophorids, dinoflagellates constitute important primary producers. Approximately half of the extant dinoflagellate taxa are autotrophic; others are heterotrophic, mixotrophic, parasitic or symbiotic. Some dinoflagellates, such as those belonging to the genus Symbiodinium, and commonly referred to as zooxanthellae, are symbionts of various organisms including corals, radiolarians and foraminifera. Many dinoflagellates have a complex life cycle involving several stages, asexual and sexual, motile and non-motile. During the course of sexual reproduction, some species form a diploid cell protected within a cyst, which permits survival of the organism during a dormancy period of variable length. The organic cyst material is called dinosporin: it has been compared to the sporopollenin of pollen grains, but shows distinct chemical macromolecular composition, which varies depending upon the taxon. The organic-walled cysts, also known as “dinocysts,” are typically 15 to 100mm in diameter. The chapter discusses the state of the art knowledge that allows for the use of dinocysts in paleoceanography, with an emphasis on the strengths and weaknesses of the methods.